2 , … , 6 0 5 3
Consider an arithmetic progression of ( n + 2 ) terms with first term 2 and last term 6053.
If the ratio between the second term and the ( n − 4 ) th term is 1 : 1 2 0 7 , find the value of n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is A 1 and not A 3 in your 4th step.
Log in to reply
Thanks I edited it.
Log in to reply
I got the answer as 4.
Log in to reply
@Ayush G Rai – Answer can never be 4, then the (n-5)th arithmetic mean never makes sense. If there is only 4 arithmetic means what is (4-5=-1)th arithmetic mean?
Log in to reply
@Ashish Menon – sorry again!!
Log in to reply
@Ayush G Rai – :) Mistakes are done only by humans :) You would get it correct next time.
Nice Question..+1
Log in to reply
You have understood the word "arithmetic means~ right?
Log in to reply
yeah , i understand English -_-
Log in to reply
@Sabhrant Sachan – No offence bro, but view reports. He tells there is only one arithmetic mean.
but instead of writing : "In between 2 and 6053 is inserted n arithmetic means" , write : " between 2 and 6053 n arithmetic means are inserted"
Log in to reply
@Sabhrant Sachan – Pi Han told that he would do that for me. ⌣ ¨
Problem Loading...
Note Loading...
Set Loading...
Let d be the common difference, a be the first term and l be the last term.
d = n + 1 l − a = n + 1 6 0 5 3 − 2 = n + 1 6 0 5 1
A 1 (first arithmetic mean) = a + d = 2 + n + 1 6 0 5 1 = n + 1 2 n + 6 0 5 3 .
A n − 5 (first arithmetic mean) = a + ( n − 5 ) d = 2 + n + 1 6 0 5 1 ( n − 5 ) = n + 1 6 0 5 3 n − 3 0 2 5 3 .
A n − 5 A 1 = n + 1 2 n + 6 0 5 3 × 6 0 5 3 n − 3 0 2 5 3 n + 1 = 1 2 0 7 1 6 0 5 3 n − 3 0 2 5 3 2 n + 6 0 5 3 = 1 2 0 7 1 1 2 0 7 ( 2 n + 6 0 5 3 ) = 6 0 5 3 n − 3 0 2 5 3 2 4 1 4 n + 7 3 0 5 9 7 1 = 6 0 5 3 n − 3 0 2 5 3 3 6 3 9 n = 7 3 3 6 2 2 4 n = 3 6 3 9 7 3 3 6 2 2 4 n = 2 0 1 6 .